Balancing Formalism and Purposivism in the Development of Islamic Family Law in Indonesia - Ismail Jalili (CV. Doki Course and Training, 2026)
This research investigates the challenges and adjustments within this legal domain, focusing on how these interpretative approaches applied and reconciled in contemporary Indonesian jurisprudence. The aim is to analyze the balance between adhering to the strict textual interpretations of Islamic law (formalism) and considering the broader objectives and social contexts (purposivism) in legal decision-making. Scholarship on this issue points to an evolving interaction between religious continuity and social transformation, influenced by Indonesia’s legal pluralism, cultural diversity, and the indigenization of Islamic legal norms. This study employs a qualitative literature review and content analysis to examine the tension between formalism and purposivism in the development of Islamic family law in Indonesia. The findings highlight that while formalism provides a necessary structure and stability, purposivism offers flexibility and responsiveness to contemporary issues such as gender equality and technological advancements. The study reveals that Indonesian judges and legal frameworks increasingly favor a purposive approach, allowing for more context-sensitive and equitable outcomes. In conclusion, the study underscores the importance of a balanced interpretative approach to Islamic family law in Indonesia, advocating for ongoing reforms and educational initiatives to enhance understanding and application of these principles. This balance is crucial for ensuring that the legal system remains relevant and effective in addressing the needs of Indonesia's diverse Muslim population while respecting its religious.